HUBUNGAN PAPARAN DEBU KAYU DENGAN KAPASITAS VITAL PARU PEKERJA PEMOTONG KAYU DI PT. X MRANGGEN JAWA TENGAH - Maratus MS, Laili; Suroto, Suroto; Ekawati, Ekawati (Jurnal Kesehatan Masyarakat (Undip), 2018)
The work cutting work produces wood dust that cause respiratory disorders. Theppurpose of thissstudy is to analyzeethe relationship of KVP to wood cutting workers in PT. X Mranggen Central Java. Worker characteristics may be a risk factor for impairment of pulmonary vital capacity ie working period, using of APD, smoking habits, exercise habits, occupational history. Theppurposeeof this research is to analyze theerelationshipoof wood dust exposureewith KVP and physical fitness to wood cutting workers in PT.  X Mranggen Demak. The typeeof research used was observational withccross-sectional studyyapproach and quantitative analysis method. The sample of this study is total sampling that is taken from the entrie population of 30 workers. The univariate analysis of this study was based on the characteristics of the workers, <5 years working period (70.0%), good use of APD (63.3%), smoking (80.0%), no exercise (73.3%), and workers had a job history (90.0%). The bivariateaanalysis using Rank Spearman Correlation (α=0.05) showed a correlation between exposure toI wood dust and pulmonary vital capacity to wood cutting workers (p value 0.012). This study is a recommendation this company and other companiesI to conduct a health check at the beginning of work, separating the wood powder storage space by the production room, providing standardized  APD, and install docting exhaust fan.